Network processor design, Vol. 2, Issues and practices (Academic, 2003)
Responding to ever-escalating requirements for performance, flexibility, and economy, the networking industry has opted to build products around network processors. To help meet the formidable challenges of this emerging field, the editors of this volume created the first Workshop on Network Processors, a forum for scientists and engineers to discuss latest research in the architecture, design, programming, and use of these devices. This series of volumes contains not only the results of the annual workshops but also specially commissioned material that highlights industry's latest network processors. Like its predecessor volume, Network Processor Design: Principles and Practices, Volume 2 defines and advances the field of network processor design. Volume 2 contains 20 chapters written by the field's leading academic and industrial researchers, with topics ranging from architectures to programming models, from security to quality of service. Describes current research at UNC Chapel Hill, University of Massachusetts, George Mason University, UC Berkeley, UCLA, Washington University in St. Louis, Linḵpings Universitet, IBM, Kayamba Inc., Network Associates, and University of Washington. Reports the latest applications of the technology at Intel, IBM, Agere, Motorola, AMCC, IDT, Teja, and Network Processing Forum